PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS MELALUI MODEL PEMBELAJARAN THE POWER OF TWO DAN THINK TALK WRITE - Tambunan, Meti; Hutagaol, Kartini (Jurnal Padegogik, 2019)
Abstract: This study aims to improve the mathematical concepts comprehension of junior high school students. This comparatively designed study was carried out by using two cooperative learning models, namely The Power of Two (TPOT) type, and the Think Talk Write (TTW) type. This study was carried out at two classes from class VII of SMPN 3 Lembang, West Bandung. The instrument used was a test of mathematical concepts comprehension on the subject of Social Arithmetic in the form of subjective tests and student response questionnaires. The findings from the results of this study are that an increase in the mathematical concepts comprehension in students who obtained the cooperative model The Power Of Two (TPOT) type is 0.85, and students who obtained the Think Talk Write (TTW) type cooperative model is 0.83, which are both in the high category. There was no significant difference in the improvement of students' mathematical concepts comprehension between students who obtained the cooperative model The Power Of Two (TPOT) type and students who obtained the Think Talk Write (TTW) type cooperative model. Students are happy with the cooperative learning model The Power Of Two (TPOT) type. Keyword: Mathematical Concepts Comprehension , Cooperative Learning, The Power Of Two (TPOT), Think Talk Write (TTW)